Stingless Bees Pollination Increases Fruit Formation of Strawberry (Fragaria x annanassa Duch) and Melon (Cucumis melo L.) - Tri Atmowidi; Taruni S. Prawasti; Puji Rianti; Fikrunnia A. Prasojo; Nalendra B. Pradipta (Tropical Life Sciences Research, 2022)
Stingless bees (Apidae: Meliponini) are distributed in tropical and subtropical areas in the world. Stingless bees are potential pollinator to increase yield of various crops species. We measured the pollination effectiveness of stingless bees, i.e., Tetragonula laeviceps in strawberry (Fragaria x annanassa) and Heterotrigona itama in melon (Cucumis melo) in the greenhouse. Pollination effectiveness of stingless bees were measured based on their visiting activities, i.e., foraging rate and flower handling time using focal sampling method. Measurements of fruit set consist of the number of fruits per plant, the number of normal and abnormal fruits, and the size and weight of fruits. Results showed that visiting activity of T. laeviceps in strawberry flowers ranged 2.33–2.73 flowers/3 min, while H. itama in melon flowers ranged 1.77–7.12 flower/3 min. Peak activities of H. itama in melon (7.12 flowers/3 min) occurred at 9.00 a.m. to 10.00 a.m., while T. laeviceps in strawberry (2.73 flowers/3 min) occurred at 11.00 a.m. to 12.00 p.m. Pollination by T. laeviceps increased 78.9% of fruit formation and reduced 16.7% of abnormal fruits of strawberry. In melon, ratio between female and male flowers was 0.03. The number of fruits produced in melon with T. itama (6.1 fruits/plant) was higher than in open field (2.6 fruits/plant) and control plants (no pollination) (0.2 fruits/plant). Pollination by H. itama increased fruit formation of melon.